Pengembangan Sistem Manajemen Gudang berbasis Web pada PT Indokretek - Muhammad Faqih Fahmi Asyifa'; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
PT Indokretek is a company engaged in the production of spice cigarettes which was established in 2008 and is located in Pagelaran District, Malang. The warehouse management process at PT Indokretek is still carried out by traditional bookkeeping, namely by recording incoming and outgoing goods in the warehouse inventory book. There is a risk of losing warehouse inventory data in the event of a work accident. In addition, people in charge are unable to access warehouse inventory information quickly, so delays in procuring goods are possible. Delays in procurement of goods could cause a negative impact on the company's production. Based on these problems, it would be very helpful if an information system could assist the warehouse management process at PT Indokretek. This software development process implements the Waterfall SDLC. A requirements analysis was conducted which resulted in 22 functional requirements and one non-functional requirement. The software is implemented with Lumen PHP framework for the server side app and Vue.js JavaScript framework for the client side app and in accordance to REST architecture. Software testing was conducted using the validation method, which resulted in all test cases matching the software requirements. Testing was also conducted using User Acceptance Testing which resulted in a user acceptance score of 90%.